Nurses’ Competence and Operational Performance: Mediating Effects of Process Effectiveness and Service Reliability - Sri Ummi Wahyuni; Mahfudnurnajamuddin Mahfudnurnajamuddin; Suriyanti Suriyanti (Economics and Digital Business Review, 2026)
This study aims to analyze the effect of competence on nurses’ operational performance, with process effectiveness and service reliability as mediating variables at Andi Makkasau Regional General Hospital, Parepare City. The research employed a quantitative design using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The population consisted of 380 nurses, and 195 respondents were selected using the Slovin formula. Data were collected through structured questionnaires measuring competence, process effectiveness, service reliability, and operational performance. The results indicate that competence has a positive and significant effect on process effectiveness, service reliability, and nurses’ operational performance. Furthermore, both process effectiveness and service reliability significantly improve operational performance. Mediation testing shows that competence indirectly enhances operational performance through improving work process effectiveness and service reliability. These findings suggest that strengthening professional competence contributes not only directly to performance but also indirectly through better work systems and more dependable healthcare services. The study implies that hospital management should prioritize competency-based training, workflow optimization, and service standardization to improve service quality. Future research is recommended to explore additional organizational or psychological factors influencing healthcare performance in broader institutional contexts.